MyEco application / Izz Fitri Hairul Sham ... [et al.] - Hairul Sham, Izz Fitri; Dzulkarnain, Nur Syahirah; Lonsiong, Rosseryn Soubin; Ramley Alan, Siti Zuraini (2021)
Global waste production is projected to increase 70% by 2050 (World Bank, 2018). The international waste issues have worsened exponentially due to various factors such as rapid population and aggressive development. Department of Statistics Malaysia (2019) stated that more than 23 000 tonnes of trash are produced each day in Malaysia alone. The amount of waste keeps on towering as the population and development keep on increasing. In 2019, the recycling rate is only 28.1% despite having a high amount of trash. Moreover, there are various diseases such as typhoid, malaria, and gastroenteritis caused by overflowing waste. Hence, the idea of the MyEco app may solve this detrimental problem. MyEco is an innovative recycling company aiming to make recycling accessible for people with only a click away. The main objective is to promote environmental awareness by encouraging the local community to apply 6R practices: Refuse, Reduce, Reuse, Recycle, Revive, and Responsible (UiTM Green Centre, 2021). This App will be the first 6R awareness application introduced in Malaysia to assist local communities in picking up their reusable items. This 6R awareness App will help locals be active mobile application users to support environmental awareness initiatives and practising a '0' waste lifestyle. Using this application, it will be more convenient because MyEco provides the pick-up service and collects the reusable items at the customer's place instead of sending them to the recycling site by themselves. This application will encourage many people to recycle daily and indirectly to reduce overflowing solid waste. The 6R concept and waste minimisation will also educate youth to be more responsible whilst cultivating a caring attitude to protect the environment. The application is available for both iOS and Android users.